Islamic Review of Posttraumatic Growth (PTG) in Adolescent Women with Dating Violence Experience - Humaira Syahnya Almas; Vikha Alya Nabilah; Karimulloh Karimulloh (UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
This study aims to determine the Islamic review of one of the psychological studies on posttraumatic growth (PTG) in adolescent women with dating violence experience. This is a literature study with a descriptive analytic approach. The result showed that Islam forbid their people for dating, these means Islam prevent their people to do dating. However, in Islam survivors who experience dating violence considered as a person who facing a test. Islam offer the concept called â€œHijrahâ€ in order to foster a positive thought for a survivors. Hijrah means shifting from something bad to a kindness, from naughtiness to truth, also from everything negative to more positive. In Indonesia with a Muslim majority population, dating violence is the second highest case of violence against women. Similar to other traumatic events, dating violence causes negative impacts to the survivors. On the other hand, previous research says that there might be positive changes experienced by trauma survivors, such as posttraumatic growth (PTG).